115k views
3 votes
Help ASAP.
i need you to please break it down ive tried and just don't understand ​

Help ASAP. i need you to please break it down ive tried and just don't understand-example-1

1 Answer

4 votes

Answer:

A) -4

Explanation:

Question


\sf evaluate \ (-4+(m+2))/(n) \ \sf when \ m=\frac23 \ and \ \sf n=\frac13

Solution

Substitute the given values of m and n into the original expression:


\sf \implies (-4+(\frac23+2))/(\frac13)

Carry out the operation in the brackets first
\sf (\frac23+3)=\frac83


\sf \implies (-4+\frac83)/(\frac13)

Now carry out the operation in the numerator
-4+\frac83=-\frac43


\sf \implies (-\frac43)/(\frac13)

Dividing by a fraction is the same as multiplying by the flipped version of the fraction (flipped = swap the numerator and denominator of the fraction we are dividing by):


\sf \implies -\frac43 / \frac13=-\frac43 * \frac31

To multiply a fraction, simply multiply the numerators and multiply the denominators:


\sf \implies -\frac43 * \frac31=(-4 * 3)/(3 * 1)=-(12)/(3)

Finally simplify:


\sf \implies -(12)/(3)=-4

User Marko Savic
by
4.9k points